Evaluasi Program Pendidikan Kesehatan Ibu Bersalin di Polindes Desa Doridungga Provinsi Nusa Tenggara Barat - Canra Muhammad Kadfi; Maman A. Majid Binfas; Al Juska Sasni Akbar (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Maternal mortality cases in Indonesia have a large number when compared to other countries in Southeast Asia in 2017. One of the breakthroughs of the Indonesian government through the Ministry of Health is the maternity health education program to reduce maternal and child mortality. The purpose of this evaluation is to describe the implementation of maternal health. This evaluation was conducted at the Polindes of Dori Dungga Village, Donggo District, Bima Regency, West Nusa Tenggara Province. The approach in this study used a type of qualitative research method. The tools used as data collectors are interviews, observation, and documentation. The results of the evaluation show first; in the historical perspective of childbirth in Doridungga Village, around 1977, assisted by a midwife helper. Second, the government provides assistance facilities to the community, especially mothers who give birth in the form of Jampersal, BPJS, and JKN. However, the availability of the budget to finance the program through BOK is still minimal. Third, the availability of the education program budget to finance enlightenment activities for pregnant women is still lacking. Fourth: the educational value of education is provided but only limited to counseling. So, with the availability of health facilities and an even distribution of health workers, all communities, especially pregnant women, plan from the start to choose to give birth at health facilities because they are assisted by midwives.